Acquired cutis laxa associated with light and heavy chain deposition disease - Reena A Majithia; Leni George; Meera Thomas; N A Fouzia (Wolters Kluwer Medknow Publications, 2018)
Acquired cutis laxa (ACL) is a rare connective tissue disorder characterized by pendulous and coarsely wrinkled skin. There have been few cases of its association to monoclonal immunoglobulin deposition disease (MIDD), which constitutes the light chain (LCDD), heavy chain (HCDD), and light and heavy chain (LHCDD) deposition disease. MIDD predominantly involves the kidney. Skin is the next common organ to be affected by HCDD, which presents as ACL. We report the case of a 40-year-old male who presented with ACL associated with LHCDD. The clinical features of ACL in the present case appeared prior to the development of clinical features related to LHCDD.